Feasibility of Kangaroo Mother Care (KMC) Implementation in Depok City, Indonesia - Amelia, Tiara (Glob Pediatr Health, 2021)
Background: The infant and neonatal mortality rate in Depok City is still high, with low birth weight (LBW) and premature births being one of the main causes. In 2018, 14 out of 41 cases of early neonatal death were due to LBW. Studies show that Kangaroo Mother Care (KMC) can prevent or reduce LBW deaths caused by hypothermia, but the implementation is still not evenly distributed. Objective: Describe KMC feasibility as a supporting material for a KMC policy umbrella at Depok City. Method: Qualitative research was conducted with a Rapid Assessment Procedure (RAP) design. A total of 56 informants were divided into 8 discussion groups, 7 in-depth interviews and 2 Focus Group Discussions (FGD). The types of informants were families and inter-sectoral officers. Thematic analysis was used to analyze the data. Results: KMC implementation feasibility in Depok City in terms of facilities and infrastructure was still limited and the quality was insufficient. The number of human resources was still limited, and the competency was still not evenly distributed. LBW family readiness can be maintained if provided with complete and accurate knowledge; therefore, a strong commitment may develop to continue KMC at home. The potential sources of KMC financing are found at health facilities and inter-sectoral; however, to use it, a legal umbrella at the city district level is necessary. Conclusions: The factors of potential financing sources need to be followed up into a priority. This is to overcome the constraints of KMC feasibility implementation.